Long-term human expansion and the environmental impacts on the coastal zone of China - Wang, Yafei; Liao, Jinfeng; Ye, Yuxuan; Fan, Jie (Frontiers in Marine Science, 2022)
Monitoring the long-term human expansions in coastal zones and evaluating their associated environmental impacts are critical to promoting a sustainable transformation of a society. This paper evaluated the long-term human expansion of reclamation, aquaculture ponds (saltern) and artificial surface in the Circum-Bohai Coastal Zone (CBCZ) of China based on the Google Earth Engine (GEE) platform and time-series land use (LU) function classification, and analyzed the impact of human expansion on the sustainability of coastal environment. Results show: (i) human activities in this coastal zone have expanded dramatically during the past 30 years, including an increase of 1555.50 km2 (+76.9%) for the reclamation area, 2065.53 km2 (+51.33%) for the aquaculture pond area, and 14329.99 km2 (+308%) for the artificial surface area; (ii) there are substantial spatial and temporal variations in human expansion in this coastal zone, mainly for Bohai Bay, Laizhou Bay, and Liaoning Bay, with the most intense expansion in the period 2003-2013, (iii) the spatial and temporal evolution of human activity expansion is strongly related to changes of water environmental quality and wetland loss, with the coupling degree of 70.73% and 79.41%, respectively. The expansion of human activity has led to a considerable loss of wetland number (from 2666.54 km2 to 1698.27 km2), indirectly affecting changes in offshore water quality. We found that human expansion is mostly driven by economic interests such as port construction, industrial parks, resource development, and tourism development, as well as a direct response to coastal zone development and protection policies.